2014
DOI: 10.1152/ajpendo.00306.2013
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor 120 signaling regulates ghrelin secretion in vivo and in vitro

Abstract: Ghrelin, an endogenous ligand for the growth hormone secretagogue receptor, is produced predominantly in the stomach. It has been reported that endogenous ghrelin levels are increased by fasting and decreased immediately after feeding and that fasting-induced ghrelin release is controlled by the sympathetic nervous system. However, the mechanisms of plasma ghrelin decrement after feeding are poorly understood. Here, we studied the control of ghrelin secretion using ghrelin-producing cell lines and found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…GPR120, which functions mainly as a receptor for unsaturated longchain fatty acids 30 , could play a role in the lipid sensing cascade in ghrelin-producing cells 31 . The decrease in octanoylated ghrelin secretion after feeding is partially induced by long-chain fatty acids that act directly on gastric GPR120-expressing ghrelin cells 32 . In addition, it was reported that the G protein α-gustducin is also involved in ghrelin octanoylation 31 and that α-gustducin could couple GPR120 33 .…”
Section: Discussionmentioning
confidence: 99%
“…GPR120, which functions mainly as a receptor for unsaturated longchain fatty acids 30 , could play a role in the lipid sensing cascade in ghrelin-producing cells 31 . The decrease in octanoylated ghrelin secretion after feeding is partially induced by long-chain fatty acids that act directly on gastric GPR120-expressing ghrelin cells 32 . In addition, it was reported that the G protein α-gustducin is also involved in ghrelin octanoylation 31 and that α-gustducin could couple GPR120 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that long-chain fatty acid receptor, GPR120, is expressed in ghrelin-producing cells and that long-chain fatty acids suppress ghrelin secretion via Gi pathway [28][29][30]. It should be noted that GPR120-mediated signaling may have affected the current experiments using palmitate.…”
Section: Discussionmentioning
confidence: 96%
“…To measure ghrelin concentrations in culture medium, the collected culture media were centrifuged, the resulting supernatants were immediately applied to Sep-Pak C18 cartridges and processed as described above. Two types of ghrelin RIA were performed: C-RIA, in which an anti-COOH-terminal ghrelin (amino acids [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] antiserum was used to detect both ghrelin and des-acyl ghrelin (total ghrelin); and N-RIA, in which an anti-NH 2 -terminal ghrelin (amino acids 1-11) antiserum was used to detect (acylated) ghrelin only, as previously described [2,17].…”
Section: Measurement Of Ghrelin Concentrations In Cells and Mediummentioning
confidence: 99%
“…Addition of GPR120 agonists, α-linolenic acid and GW-9508, into the culture medium in ghrelinoma cell lines and primary gastric mucosal cells significantly decreased ghrelin secretion. In contrast, mRNA expression levels of preproghrelin and GOAT were not changed by GPR120 agonists, but prohormone convertase 1 was suppressed by GPR120 agonists [8]. Intracellular signaling mechanisms were investigated and it was found that ERK/MAPK pathway inhibitors recovered GPR120 agonist-induced suppression of ghrelin secretion.…”
Section: Gpr120 Signaling On Ghrelin Secretionmentioning
confidence: 96%
“…G-protein coupled receptor 120 (GPR120) mRNA was highly expressed in ghrelin-GFP, SG-1, and PG-1 cells [8]. Addition of GPR120 agonists, α-linolenic acid and GW-9508, into the culture medium in ghrelinoma cell lines and primary gastric mucosal cells significantly decreased ghrelin secretion.…”
Section: Gpr120 Signaling On Ghrelin Secretionmentioning
confidence: 99%